2015
DOI: 10.1590/1982-0194201500047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de bactérias gram-negativas em portadores de HIV internados em serviço especializado

Abstract: Objective: To identify the prevalence of gram-positive bacteria in patients with HIV and who are hospitalized in specialized services. Methods: The present cross-sectional study approached 365 patients admitted in two specialized units of a teaching hospital located in the countryside of the state of São Paulo. The population was composed of 220 subjects. Sociodemographic and clinical data were obtained by means of individual interviews and medical record analysis. Saliva and nasal secretion were collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
2
1
3
Order By: Relevance
“…The laboratory findings showed high prevalence of BV (30%), mixed infection (30%), and candidiasis (10%) among HIV-seropositive women (p <0.001). But contrasts with other findings in the State of São Paulo 42 . In their study, they reported that Pseudomonas aeruginosa was the most frequently isolated microorganism, followed by Klebsiella pneumoniae in AIDs patients.…”
Section: Discussioncontrasting
confidence: 85%
“…The laboratory findings showed high prevalence of BV (30%), mixed infection (30%), and candidiasis (10%) among HIV-seropositive women (p <0.001). But contrasts with other findings in the State of São Paulo 42 . In their study, they reported that Pseudomonas aeruginosa was the most frequently isolated microorganism, followed by Klebsiella pneumoniae in AIDs patients.…”
Section: Discussioncontrasting
confidence: 85%
“…It is noted that patients with lower TCD4 lymphocyte counts are at higher risk of developing infections. 11 The length of stay in the range of 30 to 45 days is commonly linked to infections. However, there is evidence showing that there is no significant difference in the length of stay between patients.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the hospitalized person with HIV/ AIDS has a compromised immune status, some clinical situations can make the development of healthcare-related infection (HRI) easier. In addition to the immune status, this individual is exposed to numerous invasive procedures and diagnoses, making it susceptible to classic infections, whether they are of the urinary, respiratory tract or bloodstream, which makes the clinical situation more difficult (8)(9) . Consequently, these factors will directly influence the length of hospital stay and greater care attention of the nursing team.…”
Section: Introductionmentioning
confidence: 99%